1999
DOI: 10.1111/1467-9280.00151
|View full text |Cite
|
Sign up to set email alerts
|

Cross Talk Between Native and Second Languages: Partial Activation of an Irrelevant Lexicon

Abstract: Bilingualism provides a unique opportunity for exploring hypotheses about how the human brain encodes language. For example, the "input switch" theory states that bilinguals can deactivate one language module while using the other. A new measure of spoken language comprehension, headband-mounted eyetracking, allows a firm test of this theory. When given spoken instructions to pick up an object, in a monolingual session, late bilinguals looked briefly at a distractor object whose name in the irrelevant language… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

38
383
9

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 374 publications
(430 citation statements)
references
References 20 publications
38
383
9
Order By: Relevance
“…The most convincing evidence here comes from a series of studies by Marian and colleagues Marian, Spivey, & Hirsch, 2003;Spivey & Marian, 1999). Using an eyetracking paradigm with real objects, they repeatedly found that participants instructed in L2 to pick up target objects, often looked at distractor objects that were phonologically similar in L1 to the respective L2 target.…”
Section: Bilingual Word Recognition In Sentencesmentioning
confidence: 86%
“…The most convincing evidence here comes from a series of studies by Marian and colleagues Marian, Spivey, & Hirsch, 2003;Spivey & Marian, 1999). Using an eyetracking paradigm with real objects, they repeatedly found that participants instructed in L2 to pick up target objects, often looked at distractor objects that were phonologically similar in L1 to the respective L2 target.…”
Section: Bilingual Word Recognition In Sentencesmentioning
confidence: 86%
“…However, in word recognition studies, an influence of L2 proficiency on the degree of L2 interference during L1 processing has indeed been reported. For instance, being highly immersed in an L2 environment has been associated with increased interference from L2 during L1 comprehension in a visual world task (Marian, Spivey, & Hirsch, 2003;Spivey & Marian, 1999). Furthermore, the cognate facilitation effect (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…In auditory word recognition, Spivey and Marian (1999) found that Russian-English bilinguals, immersed in an Englishspeaking environment, were sensitive to form similarity between a Russian word and the English name of an object. This was shown in a visual world eyetracking experiment, in which subjects' eye movements to a visual scene where monitored as they listened to speech.…”
Section: Bilingual Language Processing Is Language Non-selectivementioning
confidence: 99%